Comparative study of nanorods and nanoflowers TiO2 thin film for heterostructure application - Razali, Fakhriah (2019)
This study introducesn-type nanorods and nanoflowers TiO2/p-type Cu2O thin film where the modification of the heterostructure between these two materials is believed to enhancethe conversion efficiencyin solar cell application.The nanorods and nanoflowers structure areexpected to improve the solar cell performance by providing better electron mobility and high specific surface area to deposit more Cu2O material for light radiation absorption.Besides, the structures were chosen due to their simple method of preparation and enhance efficiency in various applications.The n- type TiO2 thin filmswere produced using a hydrothermal method with some fabrication parameters studied during the preparation of TiO2 thin films such as Titanium Butoxide (TBOT) concentrations involving 0.07, 0.09, 0.11, 0.13 and 0.15 M. Another parameter is the duration of hydrothermal to obtain the optimum TiO2 which covered 7, 10, 13 and 16 hours of fabrication process. Next, the Cyclic Voltammogram (CV) measurement was carried out to identify the deposition parameter of p-Cu2O on TiO2/FTO substrate. Correspond to the CV measurement, -0.4V vs Ag/AgCl of potential deposition were used to develop p-Cu2O on the TiO2 layer. The construction of heterostructure was done through electrodeposition of p-Cu2O by using copper acetate based solution with pH value 12.5 at bath temperature of 60°C. The structural, morphological, optical, topological and electrical properties, were evaluated by using X-ray (XRD), Field Emission-Scanning Electron Microscopy (FE-SEM), Ultra Violet-Visible (UV-Vis), Atomic Force Microscopy (AFM) and Four-Point Probe, respectively. The TiO2 thin film exhibitsan optimum parameter at 10 hours duration of the hydrothermal process with the concentration of TBOT used was 0.9M. At the end of this study, the heterostructure thin film was successfully fabricated with a power conversion efficiency of 2x10-4%. Although low efficiency was obtained in this study, however, this finding might open a new door to the enhancement of TiO2 base for heterostructure application such as this heterojunction solar cell.